The Optimal Timing of Strategic Action – A Real Options Approach - Gordon G. Sollars; Sorin Tuluca (Journal of Entrepreneurship, Management and Innovation)

(untitled)
he possibility of a first-mover advantage arises in a variety of strategic choices, including product introductions, business start-ups, and mergers and acquisitions. The strategic management literature reflects ambiguity regarding the likelihood that a first mover can or will capture additional value. This paper uses a real options approach to address the optimal timing of strategic moves. Previous studies have modeled real options using either a perpetual or a European financial option. With these models, a strategic choice could only be made either without respect to a time frame (perpetual) or at a fixed point in time (European option.) Neither case is realistic. Companies typically have strategic options with only a limited time frame due to market factors, but companies may choose to act at any time within that constraint. To reflect this reality, we adapt a method for valuing an American financial option on a dividend paying stock to the real options context. The method presented in this paper proposes a solution for the optimum value for a project that should trigger a strategic choice, and highlights the value lost by not acting optimally. We use simulation results to show that the time frame available to make a strategic choice has an important effect on both the project value for when action should be taken, as well as on the value of waiting to invest at the optimal time. The results presented in this paper help to clarify the ambiguity that is found in the strategic management literature regarding the possibility of obtaining a first-mover advantage. Indeed, a first mover that acts sub-optimally could incur losses or at least not gain any advantage. A first mover that waits to invest at the right time based on the superior information supplied by models based on real options could be better positioned to obtain the benefits that might come from the first move.